Adolescents' Perceived Socio-Emotional Impact of COVID-19 and Implications for Mental Health: Results From a U.S.-Based Mixed-Methods Study - Rogers, Adam A.; Ha, Thao; Ockey, Sydney (Journal of adolescent health, 2021)
COVID-19 has disrupted many aspects of adolescents' lives, yet little data are available that document their subjective experiences of the pandemic. In a mixed-methods study of U.S. adolescents, we examined (1) adolescents' perceptions of how their social and emotional lives had changed during COVID-19; and (2) associations between these perceived changes and indices of their mental health, above and beyond their prepandemic mental health status. Four hundred seven U.S. adolescents (Mage = 15.24, standard deviation = 1.69; 50% female; 52%, 20% African American, 17% Hispanic/Latinx) completed surveys before (October 2019) and during (April 2020) the COVID-19 pandemic. They provided qualitative and quantitative responses on their experiences with COVID-19 and reports of their mental health. Adolescents perceived various changes in their relationships with family and friends (e.g., less perceived friend support) during COVID-19. They also perceived increases in negative affect and decreases in positive affect. These perceived social and emotional changes were associated with elevated depressive symptoms, anxiety symptoms, and loneliness in April 2020, controlling for mental health problems before the pandemic. Our findings sensitize clinicians and scholars to the vulnerabilities (changes in friendship dynamics), as well as resiliencies (supportive family contexts), presented to U.S. adolescents during the early months of COVID-19.